Comparing the Conventional and Balloon-Guided Catheter-Assisted SWIM Technology for the Treatment of Acute Ischemic Stroke - Chen, Zhengwen; Liu, Yizhi; Li, Bo; Yuan, Chen; Hou, Kaiwen; Chen, Long; Li, Peicheng (Frontiers in Neurology, 2022)
Objective Acute ischemic stroke is common in elder patients. This study investigates whether using the balloon-guided catheter (BGC) would improve the effect of stent thrombectomy (Solitaire FR With Intracranial Support Catheter for Mechanical Thrombectomy, SWIM) for patients with acute ischemic stroke due to large vessel occlusion (AIS-LVO). Method The data of 209 patients with AIS-LVO underwent SWIM were collected retrospectively from January 2017 to June 2021. These patients were divided into two groups based on whether they used of BGC or not. The propensity score matching (PSM) analysis was used to compare the differences in the first pass effect (FPE), successful recanalization, embolus escape rate, symptomatic intracranial hemorrhage (sICH), 90-day clinical favorable outcome, 90-day all-cause mortality, and complications in the patients treated with SWIM combined with balloon-guided catheter or conventional catheter. Results Among the 209 patients, 44 patients were treated with BGC and 165 patients were not. After matching, a total of 111 patients were included. The results showed that there was no statistical difference in FPE (35.1% in non-BGC group compared to 24.3% in BGC group, matched RR, 0.59; 95% CI, 0.24–1.44), successful recanalization (89.2 vs. 91.9%, matched RR, 1.37; 95%CI, 0.34–5.51), embolus escape (6.8 vs. 8.1%, matched RR, 1.22; 95%CI, 0.28–5.40), sICH (8.1 vs. 13.5%; matched RR, 1.77; 95%CI 0.50–6.24), 90-day clinical favorable outcome (48.7 vs. 54.1%, matched RR, 1.11; 95%CI 0.51–2.46), 90-day all-cause mortality (17.6 vs. 21.6%, matched RR, 1.29; 95%CI 0.48–3.47), and the incidence of complications (6.8 vs. 5.4%, matched RR, 0.79 95%CI 0.15–4.27). These results indicate that using SWIM as the first-line treatment for patients with AIS-LVO, there is no statistical significance in FPE, final successful recanalization, distal emboli, sICH, procedural time, 90-day favorable outcome, 90-day mortality, and complications with or without BGC. Conclusion Balloon-guided catheter does not affect the result of using SWIM as the first-line treatment for patients with AIS-LVO. Our results will guide daily practice, with the adoption of the use of a guided catheter without a balloon.